Effect Application of Cellulolytic Bacteria Consortium And Palm Kernel Ash on Red Chili Plants in Peat Soil - gusmawartati, gusmawartati gusmawartati; Zulfatri, Zulfatri; Nabila, Nabila (UNIVERSITY OF LAMPUNG, 2025)
Limited agricultural land in Indonesia makes peatland an alternative land for agricultural intensification. Peat soil has a low fertility, so applying cellulolytic bacteria and palm oil shoot ash is recommended. This study aimed to determine the effect of cellulolytic bacteria consortium and oil palm shoot ash on the growth and yield of red chilies on peat soils. The research was conducted in Empat Balai Village, Kampar. The study used a factorial in a completely randomized design (3x3) and three replications. The first factor was the cellulolytic bacteria consortium (0, 20, and 30 mL polybag-1), and the second factor was palm ash (0, 3, and 6 Mg ha-1 equivalent to 0.126 and 252 g polybag-1). The application of cellulolytic bacteria consortium and its interaction with oil palm shoot ash had no significant effect on all observed variables. While, the application of palm ashes significantly affected plant height, stem diameter, number of fruits, and fruits weight.